Interactions of Carbon Dioxide and Food Odours in Drosophila: Olfactory Hedonics and Sensory Neuron Properties - Faucher, Cécile P. (Public Library of Science, 2013)
Behavioural responses of animals to volatiles in their environment are generally dependent on context. Most natural odours are mixtures of components that can each induce different behaviours when presented on their own. We have investigated how a complex of two olfactory stimuli is evaluated by Drosophila flies in a free-flying two-trap choice assay and how these stimuli are encoded in olfactory receptor neurons. We first observed that volatiles from apple cider vinegar attracted flies while carbon dioxide (CO(2)) was avoided, confirming their inherent positive and negative values. In contradiction with previous results obtained from walking flies in a four-field olfactometer, in the present assay the addition of CO(2) to vinegar increased rather than decreased the attractiveness of vinegar. This effect was female-specific even though males and females responded similarly to CO(2) and vinegar on their own. To test whether the female-specific behavioural response to the mixture correlated with a sexual dimorphism at the peripheral level we recorded from olfactory receptor neurons stimulated with vinegar, CO(2) and their combination. Responses to vinegar were obtained from three neuron classes, two of them housed with the CO(2)-responsive neuron in ab1 sensilla. Sensitivity of these neurons to both CO(2) and vinegar per se did not differ between males and females and responses from female neurons did not change when CO(2) and vinegar were presented simultaneously. We also found that CO(2)-sensitive neurons are particularly well adapted to respond rapidly to small concentration changes irrespective of background CO(2) levels. The ability to encode temporal properties of stimulations differs considerably between CO(2)- and vinegar-sensitive neurons. These properties may have important implications for in-flight navigation when rapid responses to fragmented odour plumes are crucial to locate odour sources. However, the flies’ sex-specific response to the CO(2)-vinegar combination and the context-dependent hedonics most likely originate from central rather than peripheral processing.